Meri Zaat Zarra-e-Benishan: A Tale of Resistance and Resilience in the Face of Patriarchy and Misogyny-A Foucauldian Discourse Analysis - Ghilzai, Shazia Akbar; Khanam, Tahira; Fatima, Anbarin (Pakistan Journal of Humanities and Social Sciences, 2024)
This Study applies FDA (Foucauldian discourse analysis) to study how female characters resist patriarchy and misogyny in the novel “Meri Zaat Zarra-e-Benishan”. This novel is suitable for exploring female subject’s resistance because it is a true depiction of a typical patriarchal Pakistani society. This study focuses on the central ideas of FDA: power, resistance and agency. Throughout the novel protagonist Saba resists patriarchal power structures and female misogyny. She refuses to accept anything that male or female members chooses for her. She actively negotiates her position within her community. Through Saba's story, we see how both male and female misogynists can be equally damaging to women's progress, and the fight for equality. The protagonist journey is characterized by a strong sense autonomy, self-respect and self-reliance. She encounters gender based prejudices but resists actively to establish her point of view. It illustrates effectively that Pakistani women are capable of resisting repressive power structures. The findings support Foucault’s view which suggests that power circulates within the society and a powerful subject is not all powerful, conversely a weak subject is not all powerless. Rather subjects negotiate their position in everyday interactions. The subjects who are at weak positions also exhibit power which they exert through resisting powerful structures.